Telaah Kurikulum Dalam Mapel Aqidah Akhlak Di MTs IT AT-TAUHID Kampung Tauhid Sriwijaya - Khusnul Fauziah; Dia Rahma; Sindi Armita; Sapira Sapira; Nur Ayu Suci Lestari; Dwi Noviani (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Curriculum is a set of educational subjects and programs provided by an education provider institution which contains lesson plans that will be given to lesson participants in one educational level period. The method used in this research is qualitative research. According to Saryono (2010), qualitative research is research that is used to investigate, discover, describe and explain the qualities or features of social influence that cannot be explained, measured or described using a quantitative approach. The aim of this research is to discover the process of implementing the Curriculum at MTs IT At-Tauhid Kampung Tauhid Sriwijaya. The approach used in this research is qualitative with descriptive analysis methods. Data collection techniques were carried out through interviews and observation.